2005
DOI: 10.1109/tpel.2004.839810
|View full text |Cite
|
Sign up to set email alerts
|

Measurement and Control of Torque Ripple-Induced Frame Torsional Vibration in a Surface Mount Permanent Magnet Machine

Abstract: A sensor to measure the stator torsional vibration due to torque ripple produced by a surface mount permanent magnet machine is first described. The sensor is relatively inexpensive and is straight forward to incorporate into a drive system. Experiments are performed to validate that the voltage produced by the sensor is linearly related to torque ripple amplitude. Closed-loop controllers are then described that adjust the stator current harmonics applied to the machine to achieve a commanded average torque wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(28 citation statements)
references
References 10 publications
0
24
0
4
Order By: Relevance
“…The measurements depend on how the mechanical system responds to the ripple in the torque and this response is, in general, frequency dependent. Therefore it is not possible to obtain an accurate V/Nm conversion without a precise knowledge of the mechanical response to torque ripple at each frequency [14]. The causes of stator vibration are numerous and the torque ripple is only one of these.…”
Section: A Torque Ripple Indirect Measurementmentioning
confidence: 99%
“…The measurements depend on how the mechanical system responds to the ripple in the torque and this response is, in general, frequency dependent. Therefore it is not possible to obtain an accurate V/Nm conversion without a precise knowledge of the mechanical response to torque ripple at each frequency [14]. The causes of stator vibration are numerous and the torque ripple is only one of these.…”
Section: A Torque Ripple Indirect Measurementmentioning
confidence: 99%
“…successfully measure torque harmonics of permanent magnet synchronous machines in related research [26], and SR machines [25]. To validate that the piezoelectric film can measure the harmonics resulting from torque ripple for the SRM, the excitation to a laboratory-based neutral-connected 4-phase 4-kW SR machine was adjusted to yield a change in expected torque ripple amplitude and the results compared to a model of the machine.…”
Section: Machine Modelmentioning
confidence: 99%
“…These torque harmonics will induce stator frame torsional vibration and may excite undesirable resonances on the mechanical structure attached to the motor housing. For example, recently, Beccue et al revealed a case study in which the vibrations and acoustic noises of a commercial PM synchronous motor for hybrid electric vehicle propulsion system is mainly attributed to the torsional oscillation of the stator frame [4]. Hence, there is a need to understand and minimize the stator torsional vibrations of a PM BLDC drive.…”
Section: Introductionmentioning
confidence: 99%
“…In [4] [5], the derivation of current harmonics to mitigate torsional vibration is based upon the measured vibration signal fed from a piezoelectric sensor attached to the motor mounting. Although this technique is straightforward, the need of a piezoelectric sensor and an online Fourier analysis to retrieve related vibration harmonic amplitudes/phases has increased the complexity and cost of the system.…”
Section: Introductionmentioning
confidence: 99%